Recruitment and Retention of Assessment Personnel - Simpson, Cynthia G.; Lynch, Sharon A.; Spencer, Vicky G. (Journal of the American Academy of Special Education Professionals, 2007)
With a national shortage of special education personnel, including assessment personnel (Caranikas-Walker; Shapley, Cordeau, 2006; Karr, 2005), rural communities face serious challenges in retaining and recruiting highly qualified special education staff due to limited access to university training programs (Hausman & Hausman, 2003; Knapczyk, Chapman, Rodes, & Chung, 2001). This article presents research-based methods that rural school districts can use to recruit and retain assessment personnel. Many of the steps that are helpful for recruiting and retaining assessment personnel are either not utilized or underutilized (Caranikas-Walker et al.; Simpson & Lynch, 2005). Factors for assessment personnel that influenced their decision to accept a position and to stay in their positions are discussed.